2008
DOI: 10.1088/0957-4484/20/1/015101
|View full text |Cite
|
Sign up to set email alerts
|

Process entanglement as a neuronal anchorage mechanism to rough surfaces

Abstract: The organization of neurons and glia cells on substrates composed of pristine carbon nanotube islands was investigated using high resolution scanning electron microscopy, immunostaining and confocal microscopy. Neurons were found bound and preferentially anchored to the rough surfaces; moreover, the morphology of the neuronal processes on the small, isolated islands of high density carbon nanotubes was found to be conspicuously curled and entangled. We further demonstrate that the roughness of the surface must… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(90 citation statements)
references
References 32 publications
3
85
0
2
Order By: Relevance
“…The precise mechanism by which pristine, hydrophobic CNTs provided a prime substrate for neural growth is not known. CNT roughness and the large exposed surface might play an important role in their ability to favor neuronal adhesion [24] . A further possibility is that CNTs could be selectively coated by serum proteins such as fibrinogen and apolipoproteins [25] thus favoring cell adhesion.…”
Section: Cnts Sustain Neuronal Survival and Promote Neuronal Outgrowthmentioning
confidence: 99%
See 1 more Smart Citation
“…The precise mechanism by which pristine, hydrophobic CNTs provided a prime substrate for neural growth is not known. CNT roughness and the large exposed surface might play an important role in their ability to favor neuronal adhesion [24] . A further possibility is that CNTs could be selectively coated by serum proteins such as fibrinogen and apolipoproteins [25] thus favoring cell adhesion.…”
Section: Cnts Sustain Neuronal Survival and Promote Neuronal Outgrowthmentioning
confidence: 99%
“…Regarding the mechanism of attachment of cell processes to CNT substrates, Sorkin et al [24] observed that this type of cells tend to intertwine, bend and curl when cultured on a substrate that possesses a roughness comparable with the length scale of its processes (as CNTs are). High resolution scanning electron microscopy (SEM) images revealed that the curly appearance of the processes results from their curling and looping around the CNT surfaces.…”
Section: Patterned Cnt Substrates For Cell Culture Growthmentioning
confidence: 99%
“…CNT electrodes can be used to position and form stable networks due to the stable and strong physical interactions between the neurons and the CNTs. (Sorkin et al, 2009). The neurons move towards CNT covered surfaces and single neurons move particularly towards the CNT surfaces (Galvan-Garcia et al, 2007).…”
Section: Surface Topographymentioning
confidence: 99%
“…Since then studies on neuronal growth and interactions with CNTs have increased tremendously. CNTs tend to create an effective anchoring site for neurons and glial cell differentiation (Jang et al, 2010;Sorkin et al, 2009). CNT coated surfaces are neuro-adhesive in in vitro scenarios (Galvan-Garcia et al, 2007).…”
Section: Biocompatibiltymentioning
confidence: 99%
See 1 more Smart Citation